2017
DOI: 10.1111/joes.12201
|View full text |Cite
|
Sign up to set email alerts
|

From the Lab to the Field: A Review of Tax Experiments

Abstract: Tax experiments have been gaining momentum in recent years, although this literature dates back several decades. With new developments in methods and data availability, tax experiments have gradually moved away from lab settings and towards the field. This movement from the lab to the field has happened against the background of the ‘credibility revolution’ in applied economics, which has seen more rigorous methods applied to policy relevant questions, and of the availability to researchers of administrative d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
63
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(69 citation statements)
references
References 76 publications
4
63
0
2
Order By: Relevance
“…Taxpayers with longer names were abbreviated automatically after the 14th character. In line with the best practice in behavioural economics (BIT 2012) and in the empirical tax experiments literature (Hallsworth 2014;Mascagni 2016), all messages were addressed to taxpayers using their names and were simple and concise -five short sentences at most. To maximise reach and facilitate understanding, our messages were translated in two languages: English and Kinyarwanda.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Taxpayers with longer names were abbreviated automatically after the 14th character. In line with the best practice in behavioural economics (BIT 2012) and in the empirical tax experiments literature (Hallsworth 2014;Mascagni 2016), all messages were addressed to taxpayers using their names and were simple and concise -five short sentences at most. To maximise reach and facilitate understanding, our messages were translated in two languages: English and Kinyarwanda.…”
Section: Methodsmentioning
confidence: 99%
“…Although most tax experiments in the literature do not take spillovers explicitly into account (Mascagni 2016), recent studies have shown that they can be sizeable (Drago, Mengel, and Traxler 2015;Carrillo, Castro, and Scartascini 2016). Although we do not formally consider spillovers across firms, we use cluster-corrected standard errors based on districts.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical findings from both lab experiments and field research made it increasingly clear that, in the real world, taxpayers are unsure about their chances of getting audited, and this has a considerable effect on their compliance decision (Andreoni, Erard, and Feinstein 1998;Beck, Davis, and Jung 1991;Kleven et al 2011;Slemrod, Blumenthal, and Christian 2001;Spicer and Hero 1985;Thomas and Spicer 1982). Uncertainty with regard to the risk of facing a penalty for evasion tends to make taxpayers overly cautious, resulting in increasing compliance (Mascagni 2017).…”
Section: Hypothesismentioning
confidence: 99%
“…Most of these studies were conducted in the US, although a few were conducted in developed countries. Therefore, there are still some gaps in the literature, particularly in regard to the implementation of this method in developing countries (Mascagni, 2016). …”
Section: Methodological Developments In the Behaviour Economics Approachmentioning
confidence: 99%